Structural and Electrical Specification of ZrO2 nano thin film prepared by PLD - Hikmat, Suroor; A. Jumah, Thamir (Al-Nahrain Journal of Science, 2021)
Zirconium dioxide was Prepared as a thin films by using pulse laser deposition (PLD). Subsequently, the films had been thermally treated by annealing process at temperature 450 ᵒ C. The structural and electrical properties of the films were study. The electrical properties, such as Hall Effect of the ZrO₂ films were calculated. Structural properties, such as phase structure were also measured. As-deposited films were amorphous and had a large surface density of ablated particles. The Annealing process resulted change the phase from amorphous to polycrystalline. The X-ray diffraction of all these films have a polycrystalline structure. The crystalline phases of all the films are have mix of two phases were tetragonal and monoclinic phase. From Hall measurements appear that charge carriers of all these films were p-type and from AC results measured showed the films have resistance and capacitance properties.